Preserving the Ancestral Heritage as Diaconal Role of the Church Against Land Exploitation in Toba Land - Butar-butar, Manuel Citra Permata; Sinaga, Lamria (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
This article examines the church's role in preserving ancestral heritage and cultural identity in the Toba Lake region, amid increasing resource exploitation and economic pressures. Many Batak communities are being pressured to relinquish their land, resulting in the erosion of their livelihoods and traditional values. This article aims to articulate a theological and pastoral framework for church involvement in land justice and cultural preservation. Using a qualitative method grounded in contextual theological reflection and socio-cultural analysis, the research draws from biblical principles, particularly the theology of land, stewardship, and Imago Dei. Intersecting them with Batak Toba customs. The findings suggest that churches can serve as prophetic mediators by fostering partnerships among communities, governments, and investors, and by strengthening vulnerable communities through holistic diakonia. This includes education, advocacy, and economic empowerment. Theologically grounded and culturally rooted, this approach empowers churches to be agents of justice, dignity, and sustainable development.